Participation in Professional Training and Non-Economic Effects for Workers in Russia - Natalia Karmaeva; Andrey Zakharov (Journal of Economic Sociology, 2021)
The goal of the paper is to identify the relationship between participation in professional training financed by the employer and its non-economic effects: subjective control and job satisfaction (including satisfaction with pay and with professional growth opportunities). According to the human capital theory, participation in professional training accumulates both specific and general human capital; workers develop their skills and become more flexible in the labor market. We test the hypothesis that participation in professional training will be positively interrelated with employees’ subjective control and job satisfaction. The empirical base of the study is formed by the Russian Longitudinal Household Monitoring Survey (RLMS—HSE), waves 19 and 20 (2010 and 2011). The analysis identified positive effects only in the case of subjective control, but not for job satisfaction. This partially supports our hypothesis. The results show that workers who participated in professional training, compared to the workers who did not, will have a higher level of subjective control, i.e., workers feel more in control of their circumstances at work and in life. However, no effect of training was found in the case of job satisfaction. A possible reason is that training is not sufficiently integrated in the short career structures of low- or middle-skill jobs. Therefore, participation in professional training does not widen professional mobility opportunities in this labor market segment and thus is not associated with higher job satisfaction.